Trajectories of childhood anxiety disorders in two generations at high risk. Issue 6 (14th February 2020) - Bushnell, Greta A.; Talati, Ardesheer; Wickramaratne, Priya J.; Gameroff, Marc J.; Weissman, Myrna M.
Abstract: Background: The course of anxiety disorders during childhood is heterogeneous. In two generations at high or low risk, we described the course of childhood anxiety disorders and evaluated whether parent or grandparent major depressive disorder (MDD) predicted a persistent anxiety course. Methods: We utilized a multigenerational study (1982–2015), following children (second generation, G2) and grandchildren (third generation, G3) of generation 1 (G1) with either moderate/severe MDD or no psychiatric illness. Psychiatric diagnoses were based on diagnostic interviews. Using group‐based trajectory models, we identified clusters of children with similar anxiety disorder trajectories (age 0–17). Results: We identified three primary trajectories in G2 ( N = 275) and G3 ( N = 118) cohorts: "no/low anxiety disorder" during childhood (G2 = 66%; G3 = 53%), "nonpersistent" with anxiety during part of childhood (G2 = 16%; G3 = 21%), and "persistent" (G2 = 18%; G3 = 25%). Childhood mood disorders and substance use disorders tended to be more prevalent in children in the persistent anxiety trajectory. In G2 children, parent MDD was associated with an increased likelihood of being in the persistent (84%) or nonpersistent trajectory (82%) versus no/low anxiety trajectory (62%). In G3 children, grandparent MDD, but not parent, was associated with an increased likelihood of being in the persistent (83%) versus nonpersistent (48%) and no/low anxiety (51%) trajectories. Conclusion: Anxiety trajectories move beyond what is captured under binary, single time‐point measures. Parent or grandparent history of moderate/severe MDD may offer value in predicting child anxiety disorder course, which could help clinicians and caregivers identify children needing increased attention and screening for other psychiatric conditions.